Paleosecular variation and GAD studies of 0-2 Ma flow sequences from the Aleutian Islands, Alaska (Dataset) ... - Stone, David B.; Layer, Paul W. (Magnetics Information Consortium (MagIC), 2017)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleosecular variation and GAD studies of 0-2 Ma flow sequences from the Aleutian Islands, Alaska ...